A geographic relational perspective on the internationalization of emerging market firms - Deng, Ping; Delios, Andrew; Peng, Mike W. (Journal of International Business Studies, 2020)
Abstract The growth of outward foreign direct investment from emerging markets has led to increased scholarly attention on the internationalization of emerging market firms (EMFs). We break from the recent strategic approach on internationalizing EMFs to develop a problematization approach, which permits us to introduce a geographic relational perspective. We use this perspective to highlight process thinking, complex social realities, and relational practice as means by which to better develop theory on the internationalization of EMFs. Our emergent approach emphasizes the need to view EMF internationalization as deeply situated in multifaceted contextual influences, as influenced by path dependence and as manifested in practice. These three relational tenets (contextuality, path dependence, and practice) are central to our geographic relational approach’s ability to generate new challenging research questions for understanding EMF internationalization. Consequently, we add novelty to the international business domain by bringing space and process to the forefront of the EMF research agenda.